The Role of Coconut Oil in Treating Patients Affected by Plaque-Induced Gingivitis: A Pilot Study - Ripari, Francesca; Filippone, Federica; Zumbo, Giulia; Covello, Francesco; Zara, Francesca; Vozza, Iole (European Journal of Dentistry, 2020)
Objectives The aim of the study was to evaluate the coconut oil pulling efficacy as adjuvant in reducing plaque formation and in treating plaque-induced gingivitis.Materials and Methods A sample of 20 patients was divided into two groups: a study and a control group. In the study group, coconut oil, in form of mouthwash, was administered to a sample of patients affected by gingivitis, aged between 18 and 35. The protocol established a daily application of the product for 30 days, where clinical parameters for plaque formation and gingivitis—plaque index (PI), bleeding index (BI)—will be evaluated during the recalls on a specific periodontal chart. The control group did not associate a coadjuvant to the normal daily oral health procedures and the same clinical parameters were evaluated at t0 and after 30 days (t1). The data were statistically analyzed using Student’s t-test, establishing the significance level as p < 0.05.Results PI and BI decreased in both groups, with a more relevant and significant drop in the study group, from a mean value of PI of 58.0 to 19.3 and a mean value of BI of 33.5 to 5.0. In the control group, the values decreased, respectively, from 53.9 to 29.1 for PI, and from 33.5 to 16.2. Furthermore, no significant side effect was reported during coconut oil pulling therapy.Conclusions The collected data showed significant and promising improvements in reducing plaque formation and gingivitis. However, further researches have to be performed to have more consistent and statistically significant data on larger samples and to fully understand the mechanisms of action and effectiveness.
Keywords: gingivitis; coconut oil; oil pulling; oral hygiene